Polydopamine-functionalized nanographene oxide: a versatile nanocarrier for chemotherapy and photothermal therapy. (28th June 2017) - Zhang, Xinyuan; Nan, Xu; Shi, Wei; Sun, Yanan; Su, Huiling; He, Yuan; Liu, Xin; Zhang, Zhong; Ge, Dongtao
Abstract: For releasing both drug and heat to selected sites, a combination of chemotherapy and photothermal therapy in one system is a more effective way to destroy cancer cells than monotherapy. Graphene oxide (GO) with high drug-loading efficiency and near-infrared (NIR) absorbance has great potential in drug delivery and photothermal therapy, but it is difficult to load drugs with high solubility. Herein, we develop a versatile drug delivery nanoplatform based on GO for integrated chemotherapy and photothermal therapy by a facile method of simultaneous reduction and surface functionalization of GO with poly(dopamine) (PDA). Due to the excellent adhesion of PDA, both low and high solubility drugs can be encapsulated in the PDA-functionalized GO nanocomposite (rGO-PDA). The fabricated nanocomposite exhibits good biocompatibility, excellent photothermal performance, high drug loading capacity, an outstanding sustained release property, and efficient endocytosis. Moreover, NIR laser irradiation facilitates the release of loaded drugs from rGO-PDA. These features make the rGO-PDA nanocomposite achieve excellent in vivo synergistic antitumor therapeutic efficacy.